2006
DOI: 10.2991/jnmp.2006.13.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Dominant Behaviour of Quadratic Systems

Abstract: We study the dominant terms of systems of Lotka-Volterra-type which arise in the the mathematical modelling of the evolution of many divers natural systems from the viewpoint of both symmetry and singularity analyses. The connections between an increase in the amount of symmetry possessed by the system and the possession of the Painlevé Property are noted. For specific values of the parameters of the system we see that possession of the Painlevé Property is characterised by a Left Painlevé Series rather than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This does reinforce the close relationship between the Lie and Painlevé analyses observed previously [28,45,49,5,6]. In the case of rational n, it was shown that, for specific values of n in the range (1, quadrature (2.47) cannot, as yet, be evaluated for these values, noting the results in [60] and [10] we believe that the evaluation thereof is only a matter of time and effort.…”
Section: Discussionmentioning
confidence: 47%
“…This does reinforce the close relationship between the Lie and Painlevé analyses observed previously [28,45,49,5,6]. In the case of rational n, it was shown that, for specific values of n in the range (1, quadrature (2.47) cannot, as yet, be evaluated for these values, noting the results in [60] and [10] we believe that the evaluation thereof is only a matter of time and effort.…”
Section: Discussionmentioning
confidence: 47%
“…In the search for solutions of differential equations, one discovers the beauty of the algebraic properties that the equations possess. Even though closed-form solutions are the primary objective, one cannot ignore the interesting properties of the equations [1][2][3][4][5][6]. In recent years, one such area in relativistic astrophysics involves the embedding of a four-dimensional differentiable manifold into a higher dimensional Euclidean space which gives rise to the so-called Karmarkar condition for Class I spacetimes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Paul Painlevé took these ideas and classified ordinary differential equations (ODEs) of second order according to the type of singularities of their solutions [8]. Since then, the property has been used to construct symmetries, to find explicit solutions, to detect control parameters, and so on [9,10]. Basically, a system of ODEs has the Painlevé property if its general solution has no movable critical singular points.…”
Section: Introductionmentioning
confidence: 99%